Human and Created: Expanding the Common Good with Integral Ecology - Marcelli-Chu, Monica (Horizons, 2025)
This article shows how the integral ecology of Laudato Si’ expands the concept of the common good to include the natural world through recognition of and solidarity with human good. It makes this argument in dialogue with the Catholic social thought of M. Shawn Copeland on the problem of the common good in the human community and the manner in which the praxis of solidarity works to resist bias and promote authentic encounter. First, Copeland’s approach, as developing Bernard Lonergan and in dialogue with Charles Taylor, introduces the question of authentic expansion of common good to the others of history. Second, integral ecology expands the problem of the common good to both human and nonhuman others, affirming the interrelated good of human and ecological systems, and recognizing the interrelated agency that contributes to the emergence of value for common good.